What remains of the theory of demand management in a globalizing world? - Amit Bhaduri (Levy Economics Institute of Bard College, 2014)
In our era of global finance, the theory of aggregate demand management is alive and unwell, says Amit Bhaduri. In this policy brief, Bhaduri describes what he regards as a prevalent contemporary approach to demand management. Detached from its Keynesian roots, this "vulgar" version of demand management theory is being used to justify policies that stand in stark contrast to those prescribed by the original Keynesian model. Rising asset prices and private-debt-fueled consumption play the starring roles, while fiscal policy retreats into the background. Returning to foundations laid down by Keynes and Kalecki, Bhaduri sets out to clarify whether there is any place for traditional demand management policies - featuring an active role for deficit spending and public investment - in the context of financial globalization. His conclusion: such policies are ultimately unavoidable if we are to revitalize the real economy and achieve stability.
Keywords: 330